The HIPC Initiative, MDRI and Nepal: A Re-examination - Pant, Bhubanesh; Subedi, Biggyan (NRB Economic Review, 2008)
The HIPC Initiative was established in 1996 with the prime goal of reducing eligible countries’ debt burdens to the thresholds fixed under the Initiative. There are both costs and benefits associated with participation under the Initiative. For many interim HIPCs, the challenges in meeting their completion point triggers pertain to maintaining macroeconomic stability, preparing participatory Poverty Reduction Strategy Papers (PRSPs) as well as other country-specific triggers. At the completion point, full debt cancellation under the MDRI is granted. Nepal is one of the ten pre-decision point countries potentially eligible for participation under the Enhanced HIPC Initiative. The possible conditions linked to the country’s entry to the HIPC Initiative, the level of existing concessionary foreign assistance that could be non-concessionary and the likely possible debt situation after reaching the completion point are some of the issues that need a reexamination.